A Study of Citizenship Behavior for Thai Society - Nakatok, Somkait; Bureekul, Thawilwadee; Sompong, Tossapon (King Prajadhipok’s Institute Journal, 2021)
This paper reports the results of an action research project titled A Study of Citizenship Behavior for Thai Society. The main objective of the study is to develop a model for citizenship and political efficacy of citizens. The research uses an action research model that applied a participatory public policy process as an operational tool in four local government (LG) areas. In each area a representative sample of 60 subjects was evaluated to assess pre-test and post-test citizenship levels and participation in the policy development process. Statistical methods are used to analyze changes in, and the relationship between, citizenship and political efficacy. Qualitative and quantitative data are analyzed to develop models of citizenship and political efficacy of citizens. The results showed that the resulting model of the participatory public policy development process was able to increase participants’ levels of citizenship and political efficacy. Changes in citizenship behavior were found to have a positive relationship with political efficacy. The model developed for the study has imperative internal factors: 1) building a partnership between the civil sector and the LG from the beginning of the policy-making process; 2) the presence of public issues currently not addressed in policy that can be developed as policy through public-LG cooperation; 3) the LG is the primary management unit concerning the problem at hand; 4) local executive leadership; 5) there is a target agency to which policy proposals will be directed; and 6) the people who participate in the process have a high degree of enthusiasm. At the same time, external factors include 1) the presence of academic organizations as a linkage between the civic and public sectors, and 2) processes use participatory techniques. The participatory public policy development model can be applied for the creation of citizenship in a democratic society by using policy development as a tool for decentralizing democracy to the community level and strengthening partnership work to create local governance. This includes strengthening the democratic mode of life at the local level. Besides, this participatory public policy development model can be used to support the National Strategy (2018 - 2037). Participatory public policy development, with citizens feeling ownership of national development, is both a means for driving the national strategic plan and an end in itself under that plan.